Detection of antibodies to the hepatitis E virus in domestic reindeer (Rangifer tarandus) in the Republic of Sakha (Yakutia) - Vera S. Kichatova; Ilya A. Potemkin; Fedor A. Asadi Mobarkhan; Tatyana D. Rumyantseva; Sergey I. Semenov; Karen K. Kyuregyan; Mikhail I. Mikhailov (Вопросы вирусологии, 2023)
Introduction. Although domestic pigs and wild boars are the main reservoir of zoonotic hepatitis E virus (HEV) genotypes in temperate countries, the presence of antibodies to HEV (anti-HEV) in the indigenous population of circumpolar territories, i.e. outside the habitat of wild and domestic pigs, indicates the presence of an alternative reservoir of the virus. Reindeer (Rangifer tarandus) may be a potential reservoir for HEV in the polar regions. The purpose of the study was to determine the prevalence of anti-HEV among domestic reindeer in the Republic of Sakha (Yakutia).